Kesehatan Telinga di Sekolah Dasar Negeri 11 Manado - Korompis, Amelia M.; Tumbel, R. E.C.; Mengko, Steward K. (e-CliniC, 2018)
Abstract: Ear is one of the sense organs in human that can absorb 20% of information in daily life. This study was aimed to obtain the ear health status of students in SD Negeri 11 (elementary school) Manado. This was an observational descriptive study with a cross sectional design. The ear health was determined by examination of outer ear (auricle), middle ear (ear canal), and tympanic membrane. There were 25 subjetcts in this study. The examination of auricle resulted in all subjects (100%) had normal auricle. The examination of ear canal obtained 17 subjects (68%) had normal ear canal. Cerumen was found in right ear canal of 3 subjects (12%) and in left ear canal of 5 subjects (20%). The examination of tympanic membrane showed all students (100%) had normal membrane. Conclusion: Most students of SD Negeri 11 Manado had good ear health status.Keywords: ear healthÂ Abstrak: Telinga merupakan salah satu alat indra penting yang dapat menyerap sebesar 20% informasi dari kehidupan sehari-hari. Penelitian ini bertujuan untuk mendapatkan gambaran kesehatan telinga pada siswa SD Negeri 11 Manado. Jenis penelitian ialah deskriptif observasional dengan desain potong lintang. Gambaran kesehatan telinga dilihat dengan memeriksa daun telinga, liang telinga, dan membran timpani. Hasil penelitian mendapatkan sebanyak 25 subyek penelitian. Pemeriksaan daun telinga mendapatkan semuanya normal (100%). Pemeriksaan liang telinga dengan hasil normal didapatkan pada 17 subyek (68%). Serumen didapatkan dalam liang telinga kanan pada 3 subyek (12%) dan telinga kiri pada 5 subyek (20%). Pemeriksaan membran timpani mendapatkan hasil normal pada semua subyek (100%). Simpulan: Sebagian besar siswa SD Negeri 11 Manado memiliki status kesehatan telinga yang baik.Kata kunci: kesehatan telinga